Enough is enough : building a sustainable economy in a world of finite resources - Dietz, Rob, ....-; O'Neil, Daniel W., 1977-; Daly, Herman E., 1948- (Oxon : Routledge, 2013)
We're overusing the earth's finite resources, and yet excessive consumption is failing to improve our lives. In Enough Is Enough, Rob Dietz and Dan O'Neill lay out a visionary but realistic alternative to the perpetual pursuit of economic growth – an economy where the goal is enough, not more. They explore specific strategies to conserve natural resources, stabilize population, reduce inequality, fix the financial system, create jobs, and more – all with the aim of maximizing long-term well-being instead of short-term profits. Filled with fresh ideas and surprising optimism, Enough Is Enough is the primer for achieving genuine prosperity and a hopeful future for all.